Effects of salt stress on yield and quality traits of Quinoa (Chenopodium quinoa Willd.) genotypes - Abdullah, Adrita; Akter, Sadia; Hossain, Mohammad Anwar (Acta Biologica Szegediensis, 2026)
Over 30% of the coastal cultivable land in Bangladesh is affected by salinity, necessitating the introduction of salt-tolerant crops to enhance food security and climate resilience. Quinoa (Chenopodium quinoa Willd.), a facultative halophyte, can thrive under saline conditions. This study evaluated yield and quality traits of six quinoa genotypes, including two released varieties, under long-term salt stress to identify promising materials for cultivation in Bangladesh. A pot-culture experiment was conducted in a completely randomized design with three treatments: control (EC 0 dS m-¹), moderate (EC 15 dS m-¹), and strong salinity (EC 20 dS m-¹). ANOVA revealed significant genotypic differences in key agronomic traits, including days to maturity (DM), plant height (PH), panicle weight (PW), aboveground biomass (AGB), thousand-seed weight (TSW), yield per plant (YP), and harvest index (HI). Salinity stress reduced all yield-related traits. However, GPBQ-3, GPBQ-1, and SAU Quinoa-1 maintained comparatively higher yield stability under severe salinity, as supported by stress-tolerance indices. Yield per plant showed a strong positive association with PW under both control and saline conditions. A PCA biplot indicated that GPBQ-1, GPBQ-3, and SAU Quinoa-1 were the most divergent genotypes. Considering all traits under salinity, SAU Quinoa-1, GPBQ-1, and GPBQ-3 emerge as the most promising salt-tolerant genotypes for further testing and deployment.